Effects of Team Hierarchies on Bond Investing* - Massa, Massimo; Zhang, Lei (The Review of Asset Pricing Studies, 2017)
By using a unique data set on the organizational structure of fixed-income portfolio managers, that is, mutual funds and insurance companies, we study the effects of organizational hierarchy within a fund management team on bond investing. We document that team hierarchies reduce the portfolio managers’ incentive to collect and share soft information. Funds with multiple hierarchies invest less in bonds of local firms, hold less concentrated portfolios, and herd more with the market. Overall, they deliver lower portfolio performances. We also show that changes in fund hierarchy subsequently find their way into fund behaviors.